A CASE STUDY OF AUTOCAD 2D ENGINEERING DRAWING PERFORMANCE AMONG FURNITURE AND PRODUCT DESIGN (BFPD) STUDENTS - Irawan M. R, Indera; H.M, Affandi (Proceedings of the International Conference on Education, 2017)
Automatic Computer Aided Design (AutoCAD 2D) engineering drawing is an important component in BFPD courses. This software is commonly practiced by students for product design process as part of the project development. However, there is a lack of quality in 2D engineering drawing that affects the students’ prototype making process and project progression. This paper intends to identify the problems that weakened the students’ performances of the AutoCAD 2D engineering drawings. Data were collected from the students’ examinations, assignments and independent projects. Semi structured interviews were also conducted with the students. The sample consisted of BFPD’s Year 2 and Year 3 students at the First City University College. The findings indicated that the lacking of technical skills is the main contribution of this study. Therefore, future research is needed to investigate the identified problems further and recommendations are also made to improve the syllabus